2005
DOI: 10.13031/2013.19985
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Dielectric Properties of Selected Subtropical and Tropical Fruits and Associated Insect Pests

Abstract: ABSTRACT. Knowledge of the dielectric properties of commodities and insect pests is important in developing thermal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
40
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 24 publications
9
40
0
Order By: Relevance
“…7), suggesting the increasingly important role of dipole water molecules. This is in general agreement with observations made by Guan et al (2004) for mashed potato containing 1.3% or more salt and by Wang et al (2005) for subtropical and tropical fruits.…”
Section: Effect Of Ionic Conductivity On Loss Factorsupporting
confidence: 92%
See 1 more Smart Citation
“…7), suggesting the increasingly important role of dipole water molecules. This is in general agreement with observations made by Guan et al (2004) for mashed potato containing 1.3% or more salt and by Wang et al (2005) for subtropical and tropical fruits.…”
Section: Effect Of Ionic Conductivity On Loss Factorsupporting
confidence: 92%
“…A custom built temperature test cell (Wang et al, 2003b;Wang et al, 2005) connected to an oil bath (PolyScience Products, Niles, Ill., USA) was used to control sample temperature during dielectric property measurement. The system was calibrated before each independent measurement to avoid possible variations in the connections, ambient temperature and other factors that might affect the system performance.…”
Section: Experimental Set Up and Dielectric Properties Measurementmentioning
confidence: 99%
“…The technique is not suitable for determining permittivities of granular and pulverized samples when bulk densities of such samples were established by auxiliary permittivity measurements. This method is convenient, relatively easy to use because of its ability to scan through a wide range of frequencies with desired accuracy and little or no sample preparation (Feng et al 2002;Ikediala et al 2000;Nelson 2003;Venkatesh and Raghavan 2004;Wang et al 2003Wang et al , 2005.…”
Section: Open Ended Coaxial Probe Techniquementioning
confidence: 99%
“…Some interesting findings have been reported towards the RF and microwave treatments of fruits, and nuts [14]. Dielectric behaviour of the fruit flies, medfly (egg and larvae), melon fly, Mexican and oriental flies was investigated at frequencies between 1 MHz and 1.8 GHz, and the temperatures between 20 and 60 • C. They concluded that the ionic conduction dominated the dielectric behavior in the RF range, and due to the same magnitude of the ε of the subtropical and tropical fruits and the insects, the differential heating of insects in these fruits is not possible when they are treated together in an RF system.…”
Section: Introductionmentioning
confidence: 96%